Health Literacy and Fear Avoidance Beliefs Among Women with Chronic Low Back Pain - Al-Eisa, Einas; Buragadda, Syamala; Melam, Ganeswararao (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
Purpose Low back pain is considered a major health issue universally. LBP patients may avoid certain activities due to their fear avoidance behavior. Health literacy has a huge influence on the health programs and service delivery models mainly in managing chronic low back pain. The aim of this study was to examine the relation between low back pain disability, fear avoidance beliefs’ and health literacy.Materials and Methods 227 female low back pain patients of age between 20 and 55 years were analyzed. Disability, fear avoidance, and health literacy were subjectively assessed using the Oswestry Disability Index (ODI), the Fear Avoidance Beliefs’ Questionnaire (FABQ), and the Newest Vital Sign (NVS), respectively. Pearson correlation was used to determine the association between Disability, fear avoidance beliefs’ and health literacy.Results The high disability group had significantly poor beliefs related to physical activity (FAB-PA) as well as work (FAB-W). Low disability group had adequate literacy compared to those with the high disability. Greater disability was associated with higher levels of fear avoidance beliefs related to physical activity(r=0.4; p−0.00) and work (r=0.3; p−0.00) and was negatively correlated with health literacy (r=− 0.4; p≤0.01).Conclusion The study findings showed that moderate relationship exists between disability and elevated fear-avoidance beliefs and patients with limited health literacy may have difficulty in self-management of back pain further leading to chronic disability. A multidisciplinary approach focusing on these aspects while assessing disability due to low back pain is needed.
Keywords: health information; adequate literacy; back beliefs